The Development of a Homogeneous Numerical Ocean Model for the Arctic Ocean - Galt,J. A. (1972)
A numerical ocean model driven by surface stress and a source-sink distribution is developed for a homogeneous ocean. Non-linearities, lateral friction and bottom friction are included. The basin shape can be varied to accommodate a large variety of configurations. Variable bathymetry and sources/sinks around the perimeter are included. The numerical scheme is conditionally stable and has second order accuracy in space and time. A number of test cases are run to explore the dynamic significances of the various processes represented. The possible influence of these processes on the circulation of the Arctic ocean are discussed. (Author)